Adsorption of Oleic Acid on Silica Gel Derived from Rice Ash Hulls: Experimental and Theoretical Studies - Asem A. Atia; Ahmed M. El-Nahas; Asmaa M. Marie; Laila D. Al Mahdy (Adsorption Science & Technology)
Experimental and quantum chemical calculations have been used to study the adsorption of oleic acid on silica gel derived from rice ash hulls. Characterization of the gel showed that it had a BET specific surface area of 131.7 m 2 /g and a point of zero charge (pzc) at a pH value of 3. A maximum capacity of 0.70 mmol/g was obtained for the adsorption of oleic acid onto the gel at 301 K. The free energy of adsorption, ΔG 0 301 K , was determined as −23.1 kJ/mol. The interaction of propanoic and butanoic acids as models for oleic acid with bare, mono- and di-hydrated silanol has been investigated using B3LYP and CBS-QB3 levels of theory. The dihydrated silanol model gave a ΔG 0 301 K value of −24 kJ/mol at the CBS-QB3 level which is in perfect agreement with the experimental value quoted above.